Implementation of clinical supervision in improving the ability of teachers in Islamic religious education learning - Bustami Bustami; Khairuddin Khairuddin; Nasir Usman (STAI Hubbulwathan Duri, 2022)
The head of Madrasah has a role in the performance of PAI (Islamic Religious Education) teachers, namely clinical supervision of teacher learning activities. The purpose of this study is to describe how the implementation of clinical supervision for teachers in PAI learning in SD Banda Aceh City. The type of research conducted is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. The standard of data validity in qualitative research refers to the standards of credibility, transferability, dependability, and confirmability. The data analysis technique used is descriptive qualitative analysis with data reduction techniques, data presentation, and drawing conclusions. The results of this study are the madrasah principal has carried out clinical supervision of PAI teachers in Banda Aceh City, there are three stages of the clinical supervision process, namely, the initial meeting stage, the observation stage and the final meeting stage. Of the three stages of the clinical supervision process for PAI teachers, the principal has carried out the clinical supervision process properly and correctly.